The role of salt on food and human health - Elias, M. (2019)
Throughout time, salt (sodium chloride) played an important role in human societies. In ancient times, salt was used as a form of currency and to preserve foods, such as meat and fish. Besides, salt also assumed a major importance as food flavour enhancer. However, excessive salt consumption could result in serious health problems, related with hypertension and cardiovascular diseases, although this might be a controversial topic in the near future. The World Health Organization has made several policy recommendations to reduce salt intake and even implemented some policy approaches in several countries worldwide. Nevertheless, according to the European Food Safety Authority, approximately 75% of the salt we eat is already in the foods we buy. Thus, the best way to assure an effective reduction in salt consumption is to train our taste to the flavour of low-salt foods, although there is still a long way to go from awareness to action. The main goal of this chapter is to review the social and economic importance of salt throughout human history; its role in food preservation, food safety and food sensory evaluation; the impact of salt intake on human health; and the attempts to reduce or replace salt in food.